The equilibrium crystal shape of iron. (October 2016) - Kovalenko, O.; Chikli, F.O.; Rabkin, E.
Abstract: We demonstrate that plastic deformation of submicrometer-size supported Fe particles by a hard diamond tip accelerates the evolution of their shape during annealing at the temperature of 880 °C, below the α-γ transformation temperature. Employing statistical criteria for equilibration, we found that equilibrated α-Fe crystals exhibit 011, 001, 111, and 112 facets. The work of adhesion of α-Fe to the basal plane of sapphire was found to be 2.3 J/m 2 . Graphical abstract: